Duchenne Muscular Dystrophy Fatigue Trajectories - Wei, Yi Sally; Hnaini, Mona; ElAloul, Basmah; Zapata, Eugenio; Campbell, Craig (Neuropediatrics, 2023)
Introduction Children with Duchenne muscular dystrophy (DMD) are at risk of experiencing fatigue that negatively impacts their health-related quality of life (HRQoL). This study aimed to assess the association between fatigue and HRQoL, by examining fatigue trajectories over 48 weeks, and assessing factors associated with these fatigue trajectories.Methods The study sample consisted of 173 DMD subjects enrolled in a 48-week-long phase 2 clinical trial (NCT00592553) for a novel therapeutic who were between the ages of 5 and 16 years.Results The results of regression modeling show baseline fatigue and baseline HRQoL (R2 = 0. 54 for child self-report and 0.51 for parent proxy report) and change in fatigue and HRQoL over 48 weeks (R2 = 0.47 for child self-report and 0.36 for parent proxy report) were significantly associated with one another. Three unique fatigue trajectories using Latent Class Growth Models were identified for child and parent proxy reported fatigue. The risk of being in the high fatigue group as compared to the low fatigue group increased by 24% with each year increase in age and also with decreasing walking distance, as reported by children and parent proxy, respectively.Conclusion This study identified fatigue trajectories and risk factors associated with greater fatigue, helping clinicians and researchers identify the profile of fatigue in DMD children.
Keywords: Duchenne muscular dystrophy; fatigue; health-related quality of life